The interplay of narcissism and self-construal in shaping sustainable work behavior in Indonesia collective culture - Siti Nuzulia; Anna Undarwati; Pradipta Christy Pratiwi; Dyah Ayu Rahmawati; Luthfi Fathan Dahriyanto (Cogent Psychology)
This study investigates the influence of self-construal (independent and interdependent self-construal) on the relationship between narcissism (agentic and communal narcissism) and sustainable work behavior within the collectivistic society of Indonesia. This research is important because the dynamics between narcissism and sustainable work behavior are hypothesized to vary when mediated by self-construal. This study employed a cross-sectional design with 825 government employees in Indonesia. Participants were recruited through a Google Form containing the research questionnaire, which was disseminated via WhatsApp groups in some government institutions. The findings reveal that independent self-construal negatively mediates the relationship between narcissism and all dimensions of sustainable work behavior, except for working sustainably and avoiding harm dimensions. Meanwhile, interdependent self-construal positively mediates the relationship between agentic narcissism and all dimensions of sustainable work behavior, but not for taking initiative. Both independent and interdependent self-construal also positively mediate the relationship between both forms of narcissism and all dimensions of sustainable work behavior. The results indicating that promoting a sense of interdependence among staff members may help reduce the adverse impacts of agentic narcissism and improve sustainable work practices, especially in cultures that value collectivism.